Transition framework for neglected and underutilized crop species - El Bilali, Hamid; Cardone, Gianluigi; Rokka, Susanna; De Falcis, Eleonora; Naino Jika, Abdel Kader; Diawara, Ali Badara; Nouhou, Bassirou (University of East Sarajevo, 2024)
There are thousands of neglected and underutilized species (NUS) worldwide, but only a few make it to the mainstream and spotlight. The reason for that lies probably in the dynamics of the transition from a NUS to a major crop. However, there is no transition framework that specifically addresses NUS. To bridge the gap, this paper suggests a transition framework for NUS. This work was carried out within the project SUSTLIVES (Sustaining and improving local crop patrimony in Burkina Faso and Niger for better lives and ecosystems). It draws upon a search performed on the Web of Science in July 2022. The eligible articles were analysed using the Multi-Level Perspective (MLP) on socio-technical transitions and its three elements viz. niches, socio-technical regime and socio-technical landscape: Niches refer to NUS; the socio-technical regime relates to the incumbent, dominant system of major commercial staple crops, and includes factors hindering NUS integration; and the socio-technical landscape refers to policies and macro-trends affecting both the niche and the regime. The transition dynamics and success depend not only on the characteristics of the niche NUS (cf. strengths and weaknesses), regime and landscape, but also on the type, intensity and timing of interactions among them. The interaction of elements as well as transition speed are moderated by the levers of change that lie in the areas of policy, finance and market, technology and practices, culture, and science and innovation. Further work is needed to refine and test the framework in different contexts and on various NUS.